2014
DOI: 10.1007/s10815-014-0324-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone levels as a predictor of the pregnancy rate in women of advanced reproductive age

Abstract: Purpose To investigate whether serum anti-müllerian hormone (AMH), follicle stimulating hormone (FSH), or antral follicle count (AFC) are predictive for clinical pregnancy in women who underwent IVF cycles at the age of 35 and older Methods A total of 240 consecutive women who underwent IVF cycles at the age of 35 and older were enrolled in this crsoss-sectional study. Pregnant and nonpregnant women were compared. Results The median AMH level of pregnant women was higher than non-pregnant women [3.20 (0.63-9.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
(32 reference statements)
1
19
0
4
Order By: Relevance
“…Although some studies have reported that AMH can be a predictor of the ovarian reserve and the success rate of IVF,20, 21 this study's findings are consistent with those of other studies 22, 23…”
Section: Discussionsupporting
confidence: 90%
“…Although some studies have reported that AMH can be a predictor of the ovarian reserve and the success rate of IVF,20, 21 this study's findings are consistent with those of other studies 22, 23…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have associated higher AMH concentrations (Kamel et al 2014, Sahmay et al 2014 and AFC (Holte et al 2011) with higher pregnancy rates in women undergoing reproductive treatments. However, longitudinal studies on plasma AMH at the prepubertal age and its implications in later reproductive life in girls and domestic animals are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to in part the declining ovarian reserve as evidenced by low levels of anti-Mullerian hormone (AMH) and antral follicular counts (AFC) which are proxy indicators of the ovarian reserve [13]. Both of our patients had AMH levels in the low fertility range.…”
Section: Discussionmentioning
confidence: 78%